Application of Android-Based SDIDTK Development Stimulation Media on the Developmental Abilities of Preschool - Setiawati, Santun; Sulastri, Titi; Ningsih, Ratna; Skriptini, Ayu Yuliani; Dermawan, Agus Citra (Poltekkes Kemenkes Jakarta III, 2024)
A nation's future depends on children's success in achieving optimal growth and development. One of the efforts to achieve optimal development is screening and developmental stimulation. Implementation of development stimulation requires media. The media used is android-based media designed by researchers, including gross and fine motor stimulation, speech and language, as well as socialization and independence. The purpose of this study was to determine the effect of developmental stimulation media on the developmental abilities of preschoolers. The method used is a quasi-experimental design test analysis using univariate analysis (frequency distribution) and bivariate (Wilcoxon tests). The number of respondents was 75 (35 children in the intervention group and 35 children in the control group). In the intervention group, development stimulation was carried out using an android-based development stimulation media SDIDTK while in the control group used PPT material after the post-test. The results showed that there was a significant difference between average ability: gross movement, fine movement, speech and language, and socialization and independence of children in the intervention group and the control group after treatment (p-value < 0.005 and α= 0.05). IT-based stimulation media (android) can be used as an alternative in stimulating development in preschool-aged children.